Decentralization and institution building: Emergence and development of the Consejos Departamentales de Alcaldes in El Salvador - Andrea Kramer (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2003)
The Consejos Departamentales de Alcaldes (CDAs) are departmental extensions of the National Corporation of Municipalities (COMURES) and emerged as new institutions in the decentralization process in El Salvador. Their organisational structure and function, as well as future role in the decentralization process is currently under intense debate. The paper places special emphasis on the role of external actors or, more specifically, agencies of development assistance such as the United States Agency for International Development (USAID) or the German Agency for Technical Cooperation (GTZ). Building and strengthening institutions plays a predominant role in development cooperation and the question whether institutions are amenable to design is of utmost importance to donor agencies. In this light, the paper contributes to the ongoing debate on designing policies for institution building. The paper explores the origin and development of the CDAs. Based on theoretical concepts of new institutionalism, the study analyses the reasons for their emergence as well as the explanatory factors for their contrasting developments in El Salvador's different departments. The analysis is linked to a legal assessment of the nature and competencies of the CDAs. Furthermore, the paper outlines some of the main challenges the CDAs are facing today. The study concludes that the emergence of the CDAs (in 1991) can be traced back to roughly congruent interests between USAID and the Salvadoran Government, which created coordinating bodies at departmental level for the purpose of counterinsurgency. As far as the development of the CDAs is concerned, the case studies undertaken in four different departments of El Salvador illustrate that many of the differences today can only be explained by the divergent interests of the actors involved. However, the analysis also reveals that institutions, once set in place, can take their own life, and possibly proceed into a direction not foreseen by their creators. By the same token, their development depends on the institutional environment such as macro-level structures, which usually cannot be changed by external actors. Correspondingly, the paper finds that institution building is possible, but can only be successful if the institutional context is give due consideration.
Keywords: 320; Dezentralisierung; Kommunale Selbstverwaltung; El Salvador